Effects of Dietary Cucumber Tree Leaf Extract (Averrhoa bilimbi) Supplementation on Survival and Growth Performance of Bilih Fish (Rasbora maninjau) - Islama, Dini; Diansyah, Sufal; Febrina, Citra Dina; Muliyana, Agusriati; Rahmayanti, Fitria; Diana, Farah (Journal of Fisheries and Environment, 2026)
This study investigated the effect of dietary supplementation with cucumber tree leaf extract (Averrhoa bilimbi) as a natural feed additive on the survival and growth performance of bilih fish (Rasbora maninjau). Leaves of A. bilimbi were dried, ground, and macerated in 96% ethanol (1:10 w/v) for 72 h. The solvent was evaporated, and the viscous extract was stored at 4°C prior to feed incorporation. A completely randomized design (CRD) was applied, comprising four dietary treatments with three replicates each: P0 (control, no extract), P1 (1% extract), P2 (3% extract), and P3 (5% extract) per kilogram of feed. Juvenile bilih fish measuring 2–3 cm in length were stocked at a density of one fish per liter and reared for 40 days. Feed was administered at 3% of biomass daily in two equal meals. Key response variables included survival rate and growth performance. Analysis of variance (ANOVA) revealed that dietary supplementation with cucumber tree leaf extract had a significant effect on growth performance (p<0.05) but exerted no significant influence on survival rate (p≥0.05). The optimal supplementation dose was approximately 3% (P2), with lower or higher doses resulting in reduced growth performance. A. bilimbi may be effective as a natural feed supplement for improving the growth of R. maninjau, possibly because of its bioactive compound content and the slight increase in the dietary protein level.